Digital innovation in higher education: a questionnaire to portuguese universities and polytechnic institutes - Vicente, Paulo Nuno (2021)
Over the past decade, the societal impact of digital transformation, with the prospects of a Fourth Industrial revolution, has led to an innovation imperative in European policymaking regarding Higher Education Institutions (HEIs). This article examines Portuguese universities and polytechnic institutes, the two components of the national higher education system, in order to (1) characterize digital infrastructure, networks and equipment availability (hardware and software), (2) describe the self-reported digital practices among Portuguese HEIs’ faculty members, and (3) verify the alignment between faculty members’ digital practices, teaching environment and European recommendations for digital education. The study, descriptive in nature, conducts the most comprehensive online questionnaire available to date on digital innovation in Portuguese HEIs (N=547). The main constraints to digital innovation in Portuguese higher education teaching are the limited infrastructure and resources, a conservative academic culture, a lack of funding opportunities, insufficient technological resources and technical support